2019
DOI: 10.7759/cureus.4914
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone Reduces 28-day Mortality in Septic Patients: A Systemic Review and Meta-analysis

Abstract: The goal of this study was to determine the utility of hydrocortisone in septic shock and its effect on mortality. We performed a systematic search from inception until March 01, 2018, according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines comparing hydrocortisone to placebo in septic shock patients and selected studies according to our pre-defined inclusion and exclusion criteria. Four reviewers extracted data into the predefined tables in the Microsoft Excel (Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, their results were based on a meta-analysis of only five RCTs. Systematic reviews with meta-analyses published after 2018 have shown inconsistent results regarding short-term mortality linked to hydrocortisone use in patients with sepsis (12,(47)(48)(49)(50). These disparities may arise from factors, such as the use of different steroids, application of varied statistical methods, and inclusion of participants beyond just adults with septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their results were based on a meta-analysis of only five RCTs. Systematic reviews with meta-analyses published after 2018 have shown inconsistent results regarding short-term mortality linked to hydrocortisone use in patients with sepsis (12,(47)(48)(49)(50). These disparities may arise from factors, such as the use of different steroids, application of varied statistical methods, and inclusion of participants beyond just adults with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that hydrocortisone alone demonstrated marginal benefits over placebo. In a systematic review conducted in 2019, Siddiqui et al ( 47 ) concluded that the administration of hydrocortisone significantly reduced the 28-day mortality rate among patients with refractory septic shock. However, their results were based on a meta-analysis of only five RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Such limitations make it challenging to draw definitive conclusions about the efficacy and safety of hydrocortisone. The variability in study designs and patient characteristics has hindered the ability to extrapolate findings to broader septic shock populations [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…Mortality reduction: The impact of hydrocortisone on mortality rates among septic shock patients remains a subject of ongoing debate and further investigation. While findings may exhibit variability across studies, certain trials, and systematic reviews have reported reduced mortality rates among specific subgroups of septic shock patients receiving hydrocortisone [ 16 ]. This observation underscores the nuanced and potentially lifesaving role that hydrocortisone can play in specific clinical contexts.…”
Section: Reviewmentioning
confidence: 99%
“…A 2019 systemic review and meta-analysis included five randomized controlled trials (RCTs) comparing the effects of treatment with hydrocortisone to placebo on 28-day all-cause mortality in adult intensive care unit (ICU) patients (N=5,838). 1 Patients were approximately 64 years old and 64% male. The active treatment protocol varied in the studies with two trials using hydrocortisone 50 mg IV every six hours plus fludrocortisone 50 µg via nasogastric (NG) tube for seven days (n=1,570), two trials using hydrocortisone 200 mg daily continuous IV (1 trial for 7 days, and 1 for 6 days with additional 6 day taper; n=3,801), and one trial using hydrocortisone 50 mg IV every six hours for five days followed by a six-day taper (n=499).…”
mentioning
confidence: 99%